Efficiency of entomonematodes for controlling Aeneolamia varia (Hemiptera: Cercopidae) stages under controlled conditions - ROSERO-GUERRERO, MIRIAM; BUSTILLO-PARDEY, ALEX ENRIQUE; LÓPEZ-NÚÑEZ, JUAN CARLOS; CASTRO-VALDERRAMA, ULISES; GÓMEZ-LÓPEZ, EYDER DANIEL (Revista Colombiana de Entomología, 2012)
Aeneolamia varia was reported in sugar cane crops in the Cauca Valley between 2007 and 2008 and its infestations extended to 25,000 ha, thereby threatening the sugar and “panela” industries. Given this situation, research was initiated on entomopathogenic nematodes in order to evaluate them for control of this pest. We evaluated the species Steinernema colombiense, Steinernema websteri, Steinernema sp.1, Steinernema sp.2, Heterorhabditis bacteriophora and a species of Steinernema coded as O1R1 in doses of 100 and 1,500 infective juveniles (IJ)/cm2 of spray area on the nymphal instars of A. varia in sugar cane seedlings under greenhouse conditions. The adult stage was evaluated under laboratory conditions using 100 IJ/cm2 and bioassay systems in Petri dishes and cylinders. The third nymphal instar was the least susceptible and the fourth instar was the most susceptible to H. bacteriophora, presenting a mortality of 89.1% with 100 IJ/cm2. The adult stage had 100% mortality with all nematode species tested under bioassay conditions with Petri dishes, while in cylinders the mortality varied between 40 and 54%. The experiment to demonstrate the ability of the nematode species to search for the host A. varia, revealed that all are capable of finding their nymphs, but H. bacteriophora and Steinernema sp.1 were the most efficient causing mortalities of 46% and 30%, respectively.